Comparison of epidermal growth factor receptor tyrosine kinase inhibitors for patients with lung adenocarcinoma harboring different epidermal growth factor receptor mutation types - Sojung Park (BMC Cancer, 2021)
Abstract Background Epidermal growth factor receptor (EGFR) mutations in non–small-cell lung cancer predict sensitivity to EGFR tyrosine kinase inhibitors (TKIs). EGFR mutation types are associated with efficacy of EGFR TKIs. We investigated the clinical outcomes of afatinib, erlotinib, and gefitinib according to EGFR mutation type in patients with lung adenocarcinoma. Methods Between May 2010 and December 2018, we investigated 363 patients with advanced lung adenocarcinoma harboring EGFR mutations who received EGFR TKIs. Efficacies of EGFR TKIs such as response rate, progression-free survival (PFS), and overall survival (OS) were retrospectively evaluated according to exon 19 deletion (E19del), L858R point mutation (L858R) and uncommon mutations. Results The frequency of E19del was 48.2%, that of L858R was 42.4%, and that of uncommon mutations was 9.4%. E19del and L858R were associated with superior PFS and OS compared with uncommon mutations. Erlotinib showed significantly inferior OS than other TKIs (30.8 ± 3.3 in erlotinib vs. 39.1 ± 4.3 in afatinib vs. 48.4 ± 6.3 in gefitinib; p = 0.031) in patients with L858R. Gefitinib showed significantly inferior PFS (4.6 ± 1.1 in gefitinib vs. 11.6 ± 2.7 in afatinib vs. 10.6 ± 2.7 in erlotinib; p = 0.049) in patients with uncommon mutations. Conclusion Afatinib was significantly associated with a longer PFS, presenting constant effectiveness in all EGFR mutation types. Caution may be needed on the use of erlotinib for L858R and the use of gefitinib for uncommon EGFR mutations.